Portable Electrochemical Gas Sensing System with a Paper-Based Enzyme Electrode - Shogo Kawahara; Yukio Fuchigami; Shoji Shimokawa; Yousuke Nakamura; Tatsumi Kuretake; Masao Kamahori; Shigeyasu Uno (Universitas Ahmad Dahlan, 2017)
An unconventional portable electrochemical gas sensor composed of a smartphone, a finger-sized sensing chip and a single use paper-based enzyme electrode was proposed to detect a particular target gaseous inclusion for self-breath-analysis with ease. This attempt allowed us to monitor our physical status immediately and continuously regardless of a time, place or person due to the improved convenience, immediacy, and affordability. The custom CMOS chip with the capability of performing an amperometric determination when the power voltage supplied from the earphone jack of a smartphone was designed as an analytical device. A disposable enzyme electrode was prepared simply from a chromatography paper and a commercial carbon pencil instead of the conventional indisposable material and complex manufacturing process. The quantification of ethanol in gaseous samples was demonstrated in range from 50 to 500ppm (V/V) in accord with concentrations in exhaled breath. The response current increased linearly with increasing vapor ethanol concentration.